2011
DOI: 10.1007/s00216-011-5439-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of Δ9-tetrahydrocannabinol and 11-nor-9-carboxy-Δ9-tetrahydrocannabinol in oral fluid using isotope dilution liquid chromatography tandem mass spectrometry

Abstract: The detection and confirmation of cannabinoids in oral fluid are important in forensic toxicology. Currently, the presence of Δ(9)-tetrahydrocannabinol (THC) is used for the detection of cannabis in oral fluid. A low concentration of 11-nor-9-carboxy-Δ(9)-tetrahydrocannabinol (THC-COOH) is found in oral fluid, which suggested a convenient and low-sensitivity confirmation assay can be used in a routine forensic laboratory. In this study, a highly sensitive isotope dilution liquid chromatography-tandem mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…recently reported a LCMSMS method for THCCOOH in a Quantisal-collected oral fluid with a specimen volume equivalent to 250 μL oral fluid, similar to our current method, employing solid phase extraction prior to derivatization with triphenylphosphine and 2-picolylamine prior to LC triple quadrupole MS achieving a 10 pg/mL LOQ [21]. Our current LCMSMS method achieves similar LOQs with identical oral fluid specimen volumes while avoiding costly derivatization required for these other two LCMSMS methods [21, 22]. …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…recently reported a LCMSMS method for THCCOOH in a Quantisal-collected oral fluid with a specimen volume equivalent to 250 μL oral fluid, similar to our current method, employing solid phase extraction prior to derivatization with triphenylphosphine and 2-picolylamine prior to LC triple quadrupole MS achieving a 10 pg/mL LOQ [21]. Our current LCMSMS method achieves similar LOQs with identical oral fluid specimen volumes while avoiding costly derivatization required for these other two LCMSMS methods [21, 22]. …”
Section: Discussionmentioning
confidence: 83%
“…Lee et al reported a LCMSMS method for THCCOOH in 250 μL expectorated oral fluid that employed acetonitrile precipitation, derivatization with dansyl chloride, and liquid-liquid extraction prior to LC triple quadrupole MS achieving an LOQ of 5 pg/mL [22]. Coulter et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 2-dimensional GC-MS assay was the first to quantify OF THCCOOH (LOQ = 7.5 ng/L) as well as THC, CBD, CBN, and 11-OH-THC (LOQs = 0.5-1 μg/L). [215] In the past year, LC-MSMS, [186, 216] microflow LC-MSMS, [217-218] and isotope dilution LC-MSMS [219] methods to analyze OF for THCCOOH (LOQs = 7.5-15 ng/L) and THC (0.25-1 μg/L) were published. Chromatographic OF confirmation assays for cannabinoids published since 2003 are described in Table 6.…”
Section: Confirmatory Methodsmentioning
confidence: 99%
“…More recently, methods have been published using LC-MS/MS requiring derivatization, usually unnecessary in LC-MS/MS procedures. Lee et al reported the derivatization of THC and THC-COOH with dansyl chloride to improve sensitivity for detection in OF [53]; and Coulter et al derivatized with 2-picolylamine in the presence of triphenylphosphine to form a derivative for improved sensitivity (LOQ 0.01 ng/ml) [54]. Other methods are currently being developed and the future is certainly the simultaneous detection of THC and THC-COOH in OF using routine LC-MS/MS methods.…”
Section: Review | Moore and Crouchmentioning
confidence: 96%